Analysis of Poultry Farmers’ Utilization of Agricultural Credit in Jos South Local Government Area of Plateau State, Nigeria - Vihi, Samuel Keghter; Tanko, Philip Karik; Selzing, Peter Musa; Jesse, Birma; Ahmad, Ibrahim Ibrahim (Food, Agriculture and Natural Resources - NETWORKS, 2024)
This study analyzed poultry farmers’ utilization of agricultural credit in Jos South Local Government Area of Plateau State, Nigeria. The population for the study consists of all the registered poultry farmers in Jos South Local Government Area. Multistage sampling technique was used in selecting the respondents for the study. Primary data were collected through the use of questionnaires and interview schedule and were subjected to both descriptive and inferential statistics. Findings from the study showed that majority (86%) of the poultry farmers’ were men, with a mean age of 42 years. Majorities (89%) were married and had five people on average per home. The study also showed that 51% of the farmers were educated beyond high school with a mean farming experience of 9 years and average stock size of 1658 birds. The responders received an average credit amount of ₦357224 while the average amount utilized for poultry business was ₦290164. About 75% of the farmers utilized the loan given to expand their existing farm business. Gender, household size, farming experience and flock size were the significant determinants of agricultural credit utilization by the poultry farmers. Inadequacy of the credit amount received (58.0) and competing family needs (32%) were the main obstacles to using agricultural credit among the poultry farmers. The study recommended more budgetary allocations and farmer’s friendly policies by financial institutions to enable bigger volumes of disbursements to farmers.